(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study examines the influence of talent management, employee engagement, and leadership style on the performance of State-Owned Enterprises (SOEs). Using a quantitative approach, data were collected from employees across various SOEs and analyzed using multiple regression techniques. The findings reveal that all three factors significantly impact organizational performance, with employee engagement being the strongest predictor. Talent management plays a crucial role in attracting, developing, and retaining skilled employees, while leadership style influences motivation and overall workplace effectiveness. These results highlight the importance of strategic human resource management and transformational leadership in enhancing SOE performance. The study contributes to theoretical frameworks such as the Resource-Based View (RBV) and Job Demands-Resources (JD-R) model, reinforcing the role of human capital in organizational success. Practical implications include the need for SOEs to prioritize employee engagement initiatives, leadership development programs, and effective talent management strategies. Future research should explore longitudinal studies and incorporate objective performance measures to further validate these findings.